2013
DOI: 10.1371/journal.pone.0078970
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Multiple Infections, Recombination and Horizontal Transmission of Wolbachia in the Andricus mukaigawae (Hymenoptera; Cynipidae) Communities

Abstract: Wolbachia are maternally inherited endosymbiotic bacteria of arthropods and nematodes. In arthropods, they manipulate the reproduction of their hosts to facilitate their own spread in host populations, causing cytoplasmic incompatibility, parthenogenesis induction, feminization of genetic males and male-killing. In this study, we investigated Wolbachia infection and studied wsp (Wolbachia surface protein) sequences in three wasp species associated with the unisexual galls of A. mukaigawae with the aim of deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 58 publications
4
51
0
1
Order By: Relevance
“…Whereas Kageyama et al (2010) detected two isolates of Wolbachia (Supergroups A and B) in a population of S. paniceum, we detected only one isolate (Supergroup B). Previous studies have reported similar results for a variety of insect species (Floate et al, 2011;Malloch and Fenton, 2005;Reuter and Keller, 2003;Salunke et al, 2012;Yang et al, 2013). In addition to confirming previous reports of wsp isolates in select stored product insect, we believe our results provide the first report for Wolbachia infections in Oryzaephilus mercator (Fauvel) (Coleoptera: Silvanidae) and in Dermestes lardarius Linnaeus (Coleoptera: Dermestidae).…”
Section: Characterization Of Wolbachia With Wsp Sequencessupporting
confidence: 90%
“…Whereas Kageyama et al (2010) detected two isolates of Wolbachia (Supergroups A and B) in a population of S. paniceum, we detected only one isolate (Supergroup B). Previous studies have reported similar results for a variety of insect species (Floate et al, 2011;Malloch and Fenton, 2005;Reuter and Keller, 2003;Salunke et al, 2012;Yang et al, 2013). In addition to confirming previous reports of wsp isolates in select stored product insect, we believe our results provide the first report for Wolbachia infections in Oryzaephilus mercator (Fauvel) (Coleoptera: Silvanidae) and in Dermestes lardarius Linnaeus (Coleoptera: Dermestidae).…”
Section: Characterization Of Wolbachia With Wsp Sequencessupporting
confidence: 90%
“…Wolbachia have been described as highly recombinogenic bacteria [6,7,99]. Multiple infections with different Wolbachia are frequent in the same insect individual [98,104], affording the opportunity for recombination between different strains, including not closely related ones [6,104]. Nevertheless, a recent study found that recombination is far higher within supergroups than between them [30].…”
Section: Introductionmentioning
confidence: 99%
“…, 2003; Sintupachee et al. , 2006; Yang et al. , 2013), or by contact of haemolymph through wounds in the host's bodies (Rigaud and Juchault, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…, 2013), or by contact of haemolymph through wounds in the host's bodies (Rigaud and Juchault, 1995). Horizontal transmission was also considered the route of infection by multiple Wolbachia strains, as is frequently observed in many species of Coleoptera, Diptera, Hymenoptera and Lepidoptera (Werren et al , 1995; Jamnongluk et al , 2002; Rokas et al , 2002; Reuter and Keller, 2003; Hiroki et al , 2004; Schuler et al , 2011; Yang et al , 2012, 2013; Augustinos et al , 2014). …”
Section: Introductionmentioning
confidence: 99%